The Role of Probiotics and Prebiotics in Osteolastogenesis and Immune Relevance - Li, Datong; Liu, Yuan; Yang, Xiaobin; Kong, Lingbo (Current Medicinal Chemistry, 2021)
Osteoporosis is very common in middle-aged and elderly people, and its main feature is a disease characterized by bone mass reduction and bone microstructure changes, accompanied by a corresponding increase in the risk of fracture. This is a disease affected by many factors and is more common in postmenopausal women. Currently, the treatment of osteoporosis is mainly to prevent bone resorption and reduce the risk of fracture; a variety of drugs have been used in the treatment of osteoporosis and achieved good results. In recent years, with the in-depth study of intestinal microorganisms, a strong impact of intestinal microflora on bone metabolism in terms of immunity has been reported. It can be observed in mouse-based models, which indicates that intestinal flora may be a potential new target for changing bone mineral density (BMD). Therefore, the intestinal flora is a complex system that affects and regulates the absorption of calcium and vitamin D. It affects the permeability of the intestine through its own secretion of related influencing factors and its own activities, and further affects the secretion of human hormones and immune response. Besides that, T helper cells, lymphocytes, TNF, IL-17, and the RANKL system play a key role. The impact of probiotics and prebiotics on humans is controversial due to the scarcity of research data. However, many studies have shown that the role of probiotics in different animals varies with gender, age and hormone secretion. Changes in the intestinal flora are closely related to osteopenia and/or osteoporosis. Changing its composition and activity may be a reliable strategy for altering bone quality, although further clinical studies are needed to determine the correct human method.
Keywords: bone mineral density